Five-Minute activities for young learners - McKay, Penny; Guse, Jenni (Cambridge Cambridge University press, 2007)
Five minute activities for young learners is full of short, topical, low - resource ideas for teachers of english to children. Activities are organised around six themes : * Animals, * Journeys, * Fantasy and adventure, * The world around us, * Healthy bodies, * About me. Each theme contains activities at three levels of difficulty.
Contents, website appendix.
Keywords: English - foreign language; Language; Learning; Teaching; Activities